(untitled) (Simbiótica. Revista Eletrônica, 2025)
This article explores the impact of Game Jams, with a specific focus on GameJamPlus as a platform for cultural production, community of practice development, and fostering the gaming industry in Brazil. Using quantitative and qualitative data, the study analyzes the role of Game Jams in the training and professionalization of companies in the sector, as well as their influence on the formulation of public policies and funding calls for national culture. The study includes interviews with Márcio Filho, influential in the creation of the Legal Framework for Games in Brazil, and Juliana Brito, CEO of GameJamPlus, to provide an in-depth view of industry dynamics and collaboration in game development. The discussion is grounded in Game Studies theories related to affects, engagement, immersion, and cognition, aligning multidisciplinary perspectives from the Humanities and Applied Social Sciences, particularly Education and Communication.